Synthesis, characterisation, conformational study and antibacterial activity of N-acylhydrazone and its derivatives - Tan, Yi Ying (2023)
Researchers had examined N-acylhydrazone in great detail because of their pharmacological activities. For instance, N-acylhydrazone is found to be able to act as an antibacterial, anti-inflammatory, anticancer, anticonvulsant, antimalarial as well as antiplatelet aggregation agent. This project has successfully synthesised a carboxylic acid hydrazide and a total of ten new N acylhydrazone derivatives. The carboxylic acid hydrazide was prepared from the condensation of a carbonyl ester group and hydrazine hydrate. The carboxylic acid hydrazide produced was then reacted with various types of benzaldehyde to generate a wide variety of N-acylhydrazone derivatives. The ten compounds were synthesised with yields ranging from 35 to 74 %. The chemical structure of the generated carboxylic acid hydrazide and ten new N acylhydrazone derivatives were elucidated with the help of FT-IR, 1H NMR, 13C NMR, NOE, DEPT, HMQC and HMBC. From the spectral data obtained, it was concluded that the predominant stereoisomer of the products is with (E) configuration and cis conformer. In addition, the energy for the rotational barrier for the compounds investigated were ranged 75.26 kJ mol-1 . Besides, it iii was found that N-acylhydrazone SB (substituted) exhibited excellent antibacterial activity against Bacillus subtilis and Staphylococcus aureus with the MIC value of 31.25 μg/mL and 15.63 μg/mL, respectively by using the broth dilution method.